HUBUNGAN TINGKAT PENDIDIKAN, MASA KERJA DAN TINGKAT KEBISINGAN DENGAN STRESS KERJA DI PT. X - Rarahayu Candraditya; Endang Dwiyanti (JURNAL PENELITIAN KESEHATAN, 2017)
Job stress can be caused by workplace environmental and individual factors. Physical environment such as noise, lighting, temperature, and the odor is part of workplace environment. Based on the Health Risk Assessment document of PT. X years 2011 - 2014, it is known that noise was the greatest physical environmental hazards that can be encountered at the sites. The purpose of this study was to analyze the relationship between noise level and work stress on the workforce in PT. X. This was an observational study conducted cross-sectional. The research variables were work stress, noise, education level and years of service. The total population in this study amounted to 55 people. The sample represents 50 people which were selected from a total population using simple random sampling technique. Primary data obtained from direct measurement using job stress questionnaire and Sound Level Meter. Furthermore, the data was processed statistically using computer help with Spearman correlation test. The result showed that there were two workers who experienced severe stress in PT. X had a working environment with noise levels above 85 dBA. While 20 workers that worked at the site with a noise level below or equal to 85 dBA only suffered mild stress. Statistical analysis showed significant value of p = 0.000 (p value α = 0.05), so it can be concluded that there is a significant relationship between noise level and work stress on workers at the workshop and office in PT. X.Keywords: noise, job stress, workshop